2013
DOI: 10.1615/plasmamed.2013008538
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Human Blood Leukocytes Compared with Their Respective Cell Lines after Plasma Treatment

Abstract: Non-thermal plasma application has become a promising field of investigation in chronic wound healing research over the past few decades. In addition to its well-characterized antibacterial effects, plasma potentially promotes the growth of eukaryotic cells. To date, mainly epithelial skin cells have been examined regarding the impact of plasma treatment on chronic wound healing. However, immune cells also are involved in wound healing as well as the removal of pathogens. Therefore, we compared the survival be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…[ 29 ] While many reports point to a selectivity of gas plasma treatment to induce toxic effects in tumor cells over non‐malignant cells, [ 30–33 ] more comprehensive studies revealed that selectivity depended on the type of tumor cell investigated and the cell line used for comparison. [ 34–37 ] Notwithstanding, increased expression of pro‐immunogenic surface markers in ROS‐treated cells was observed in malignant over non‐malignant cells. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] While many reports point to a selectivity of gas plasma treatment to induce toxic effects in tumor cells over non‐malignant cells, [ 30–33 ] more comprehensive studies revealed that selectivity depended on the type of tumor cell investigated and the cell line used for comparison. [ 34–37 ] Notwithstanding, increased expression of pro‐immunogenic surface markers in ROS‐treated cells was observed in malignant over non‐malignant cells. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…expression, leading to increased survival and apoptosis evasion [32]. Treatment with the apoptosis-inducing agent H 2 O 2 [33] led to an up-regulation of JNK 1/2 to 3.1-and 4.7-(p < 0.05, *) fold of the control as described in the literature [34]. Next to JNK 1/2, p38 MAPK was examined regarding its activation after non-thermal plasma treatment.…”
Section: Plasma-mediated Regulation Of Mapk Signaling Pathwaysmentioning
confidence: 90%
“…All experiments were performed with THP‐1 cells, a human monocytic cell line derived from an acute monocytic leukemia patient (CLS, Germany), and Jurkat T cells, an immortalized line of human CD4+ T lymphocyte cells (DSMZ, Germany) as previously described . Briefly, cells were cultivated once a week in Roswell Park Memorial Institute (RPMI) 1640 medium supplemented with either 8% (Jurkat) or 10% (THP‐1) fetal bovine serum, 2 mM l ‐glutamine, 0.1 mg/L streptomycin, and 100 U/ml penicillin (all Sigma–Aldrich, Germany) at 37 °C in 95% relative humidity and 5% CO 2 (Binder, Germany).…”
Section: Methodsmentioning
confidence: 99%